Cyanobacterial diversity of biological soil crusts and soil properties in karst desertification area - Chen, Qian; Yan, Ni; Xiong, Kangning; Zhao, Jiawei (Frontiers in Microbiology, 2023)
As an important component of biological soil crusts (BSCs) and the primary stage of crust succession, cyanobacteria communities occupy an important ecological niche and play an important ecological service function in desertification areas represented by deserts. In this study, we focused on the karst desertification area, which also belongs to the same category of desertification, three study areas, Guanling-Zhenfeng Huajiang (HJ), Bijie Salaxi (SLX) and Shibing (SB) in Guizhou Plateau, which represents the overall ecological environment of south China karst, were selected to conduct surveys on cyanobacteria species diversity of BSCs and soil properties. Analysis on cyanobacteria communities and physicochemical properties, via the Shannon-Wiener diversity index, principal component analysis and redundancy analysis revealed that: (1)The cyanobacteria of the three study areas are all common species, with a total of 200 species in 22 genera, 2 classes, 5 orders and 6 families, belonging to the Oscillatoriales (39%), Scytonematales (24.5%), Chroococcales (23%), Nostocales (11.5%) and Rivulariales (2%). (2)The number of species increased with the intense of karst desertification, while Oscillatoriaceae is the dominant family in HJ, the moderate-severe desertification, and Chroococcaceae and Scytonemataceae are dominant in the mild and potential desertification area SLX and SB. (3)The Shannon-Wiener diversity indexes were SLX(3.56) > SB (3.08) > HJ (3.01), indicating species were more evenly distribute in mild desertification. (4)Under the carbonate background, Shrubbery has the largest number of cyanobacteria species, compared to grass land, bare land ,and arbor woodland, however, the highest number is documented in arbor woodland in dolomite karst. (5) The soil is from weathered limestone soil or yellow soil in all three areas, and with pH ranging from 5.73 to 6.85, dominating by fine sand, and soil nutrients increase with the intense of desertification. (6) Redundancy analysis showed that organic carbon, soil moisture content (0-5cm) and total nitrogen significantly influenced cyanobacteria diversity. These results revealed the difference of soil nutrient content plays an important role in regulating the diversity and composition of cyanobacteria, which will lay a foundation for further research and application of soil ecological restoration of cyanobacteria in BSCs in karst desertification areas.